Meningkatkan Kinerja Organisasi: Peran Penghargaan Sosial dan Pengambilan Keputusan Partisipatif - Widianti, Hesti; Harjanti , Ririh Sri; Kamal, Bahri (Universitas Mercu Buana Yogyakarta, 2024)
Objectives The purpose of this study was to determine the impact of social rewards and Participation in decision-making on improving organizational performance in companies in Central Java. Methodology The data used 45 employees who were used to test the research hypothesis through Partial Least Square (PLS) modeling. Finding The results of empirical analysis reveal that decision-making has a significant effect on job satisfaction, and social rewards have a significant effect on job satisfaction. Participation in decision-making has no significant effect on organizational performance, social rewards have no significant effect on organizational performance, and job satisfaction has no significant effect on organizational performance. Conclusion The research results show that employee job satisfaction is not always directly proportional to organizational performance.